Knowledge Sharing behavior among Faculty Members of Community Colleges in Kathmandu - KC, Sudarshan (Shahid Kirti Multidisciplinary Journal, 2025)
Knowledge has been a strategic resource for academic institutions for their sustainable development. The aim of the study is to examine the impact of organizational factors (organizational culture, reward system, organizational support and availability of information communication technology) on knowledge sharing behaviour among faculty members of community colleges in Kathmandu. The study followed deductive approach with a causal comparative research design. It employed judgmental sampling to collect data from 386 faculty members. The regression analysis in SPSS revealed that organizational factors have significant impact on knowledge sharing behaviour. Among these factors, availability of information and communication technology (ICT) had the major impact. This study contributes to address the gap on knowledge sharing literature in community colleges in Nepal. College management committees and principals can get benefit for formulating policies and strategic plans. Furthermore, this study supports them to create a culture of learning and sharing of knowledge in their colleges.